MENINGKATKAN KREATIVITAS ANAK MELALUI KEGIATAN FINGER PAINTING DI TAMAN KANAK-KANAK PAUD ABA I RAMBIPUJI JEMBER - Zuhrotun Ni'mah; Dyna Rachmawati (Universitas Negeri Makassar, 2021)
This study aims to determine the increase in creativity skills through finger painting activities at the ABA I Rambipuji Kindergarten. The approach used in this research is a qualitative approach, with the type of research being Classroom Action Research. The research subjects were 15 students and 1 teacher. With a focus on creativity research and finger painting. Data collection is observation and interviews. The data analysis technique used descriptive analysis. The type of this research is classroom action research (Classroom Action Research). In the implementation of the action, two cycles are planned which are carried out through a cycle assessment process consisting of 4 main stages, namely; 1) action planning, 2) action implementation, 3) observation and 4) reflection. Based on the results of the study, it was found that finger painting activities could increase the creativity of the ABA I Rambipuji Kindergarten children.